We can solve the equations by the following method:-

0.3x-0.2y = 4 (a)

0.2x+0.3y=23/19 (b)

Multiplying (a) with 0.2 and (b) with 0.3 we get :-

0.2(0.3x-0.2y) = 4(0.2) (a)

0.3(0.2x+0.3y) = (0.2)(23/19) (b)

0.06x - 0.04y = 0.8 (a)

0.06x + 0.04y = 0.24 (b)

adding the two equations we get :-

0.12x = 1.04

x = 8.66

Substituting the value of x in (a) we get :-

0.3(8.66) - 0.2y = 4

2.598 - 0.2y = 4

y = -7.01

0.3x-0.2y = 4 (a)

0.2x+0.3y=23/19 (b)

Multiplying (a) with 0.2 and (b) with 0.3 we get :-

0.2(0.3x-0.2y) = 4(0.2) (a)

0.3(0.2x+0.3y) = (0.2)(23/19) (b)

0.06x - 0.04y = 0.8 (a)

0.06x + 0.04y = 0.24 (b)

adding the two equations we get :-

0.12x = 1.04

x = 8.66

Substituting the value of x in (a) we get :-

0.3(8.66) - 0.2y = 4

2.598 - 0.2y = 4

y = -7.01